Analisis Pengaruh Investasi, Tenaga Kerja dan Pengeluaran Pemerintah Terhadap Pertumbuhan Ekonomi di Provinsi Papua - Bahtiar,; Marlissa, Elsyan R.; Hafizrianda, Yundy (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2026)
Papua Province; and (2) identify and analyze the macro-sectoral potential of the management of the agricultural sector in Papua Province. There are two analytical tools used, namely the LQ Index and Sectoral Classen Typology. Based on the results of data processing with LQ analysis, it was identified that the agricultural sector is the base in Jayapura, Keerom, Sarmi, Mamberamo Raya, Biak Numfor, Supiori, Kepulauan Yapen, and Waropen Regencies. As for Jayapura City, the agricultural sector is not a base because it has an agricultural LQ value of 0.48 < 1. Then, from the Sectoral Classen Typology analysis, it shows that macrosectorally and macrospatially, the management of agricultural natural resources in Papua Province in the future is very prospective for developing regional economies. This is indicated by the typology of the agricultural sector in each region in Papua, which is mostly classified as an advanced and fast-growing sector (Quadrant I) for the future, namely in Sarmi, Keerom, Mamberamo Raya, Supiori, Kepulauan Yapen, and Waropen Regencies. The sectors that are categorized as advanced and fast-growing can be used as prime sectors and priorities for development in the future, both in the short, medium, and long term, in the Province of Papua. This research aims to 1) Analyze the influence of investment on economic growth in Papua Province; 2) Analyze the influence of the amount of government spending on economic growth in Papua Province; 3) Analyze the influence of the number of labor force on economic growth in Papua Province. The number of observations in this research was 69 data points in the 2010-2021 time period in Papua Province using panel data. The data that has been collected is analyzed using descriptive analysis and 2SLS analysis according to the researcher's framework, with the Eviews and Excel programs. The research results show 1) the results of the mediation test show that investment in economic growth through labor absorption indirectly has a significant positive effect; 2) the results of the mediation test show that the variable government expenditure on economic growth through labor absorption indirectly has a significant positive effect; 3) the direct influence of the Labor variable has a positive and significant effect on economic growth (GRDP). Keywords: Investment; Government Expenditures; Labor; Economic growth